The Relationship of Teachers' Role and Students' Attitudes Towards Clean and Healthy Living Behavior In Islamic Boarding Schools - Putri Syarifah, Dewi; Nurul Fadillah, Hilda; Mahameru Kaffah, Lentera; Surury, Istianah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Clean and Healthy Living Behavior (PHBS) is a practice carried out by students, teachers, and school members as part of learning to be proactive in preventing and maintaining health and playing an active role in forming a healthy environment. Children of school age are very susceptible to disease. PHBS is often associated with the number of diseases that occur in school-aged children. The method used in this study is quantitative, with a cross-sectional study design. The sample in this study was 136 respondents using the two-stage cluster technique. Data were taken using a questionnaire from the students of SMP Pondok Pesantren Mumtaz Ibadurrahman provided data using a questionnaire. According to the research findings, factors related to PHBS are the teacher's role. The teacher's role and attitude are factors that influence PHBS. Therefore, teachers should increase their support and education to students, emphasizing the importance of implementing PHBS through the learning process and encouraging cooperation activities to clean the classroom environment. Ion activities to clean the pesantren environment.